PERANAN GURU BIMBINGAN KONSELING DALAM PEMBINAAN AKHLAK SISWA - T. Hanafia (UNISAN JURNAL, 2024)
This exploration plans to learn about the job of direction and advising educators in understudies' ethical turn of events. This study utilizes a subjective strategy. The information legitimacy test utilized is triangulation. The information sources in this exploration are the school head, boss, homeroom educator and understudies. In view of the examination results, it tends to be presumed that the direction and advising program arranging at SDIT Al Qolam is great, including; Readiness of movement programs comprising of setting goals, planning program structures like yearly, month to month and everyday projects, planning staff, is completed so the execution of the BK program can run well, so there is no covering of liabilities and obligations. c) Arrangement of fundamental offices including; Direction endlessly room gear, comprising of: Information stockpiling region and whiteboard and notice board. The execution of Direction and Advising at SDIT Al Qolam isn't great, there are a few direction and administrations that poor person been carried out ideally, this is brought about by 3 things, in particular the instructive foundation of Direction and Direction Educators which isn't straight so the administrations gave are not exactly ideal, absence of direction outreach projects and guiding, as well as time requirements. The assessment completed was bad, since it couldn't precisely quantify the viability of the BK program being executed, and the shortfall of a reasonable assessment configuration was the principal consider the trouble of estimating the outcome of the program